Assessment of Potential Herb-Drug Interactions among Nigerian Adults with Type-2 Diabetes - Amaka Ezuruike; Jose Maria Prieto (Frontiers Media S.A., 2016)
It is becoming increasingly evident that patients with diabetes do not rely only on prescription drugs for their disease management. The use of herbal medicines is one of the self-management practices adopted by these patients, often without the knowledge of their healthcare practitioners. This study assessed the potential for pharmacokinetic herb-drug interactions amongst Nigerian adult diabetic patients based on information obtained from 112 patients with type-2 diabetes attending two secondary health care facilities in Nigeria. 50% of the informants used herbal medicines alongside their prescription drugs. Worryingly, 60% of the patients taking herbal medicines did not know their identity, thus increasing the risk of unidentified herb-drug interactions. The pharmacokinetic profile of eight identified herbs taken by the patients for their disease management was obtained through a literature analysis. These were then compared against those of their prescription drugs. Several scenarios of potential herb-drug interactions were identified and their clinical relevance is discussed. The lack of clinical predictors points towards cultural factors as the influence for herb use, making it more difficult to identify these patients and in turn monitor potential herb-drug interactions. In identifying these possible interactions, we have highlighted the need for healthcare professionals to promote a proactive monitoring of patients' use of herbal medicines.